Rousseau a free community of equals - Cohen, Joshua, 1951- (Oxford : Oxford University Press, 2010)
Joshua Cohen explains how the values of freedom, equality, and community all work together as parts of the democratic ideal expressed in Rousseau's conception of the 'society of the general will'. He also explores Rousseau's anti-Augustinian and anti-Hobbesian ideas that we are naturally good.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Rousseau, Jean-Jacques, -- 1712-1778 -- Political and social views; Democracy -- Philosophy